Maxillofacial morphology in post-pubertal patients with unilateral cleft lip and palate following early vs. late secondary alveolar bone grafting - Brudnicki, Andrzej; Sawicka, Ewa; Fudalej, Piotr Stanisław (Journal of cranio-maxillo-facial surgery, 2021)
The study aimed at comparing maxillofacial morphology and burden of surgical treatment in post-pubertal patients with unilateral cleft lip and palate (UCLP) following early vs. late secondary alveolar bone grafting (SABG). In this retrospective study maxillofacial morphology was assessed on lateral cephalograms of skeletally matured patients with UCLP operated on consecutively in one center by the same method of one-stage primary cleft repair followed by SABG. Cephalometric analysis comprised 8 angular and 7 linear measurements. Maxillary growth restriction was evaluated by measuring SNA angle and Co-A and PNS-A distances. Five linear regression models with SNA, SNB, ANB, Co-A, and MP/SN as dependent variables and age at primary cleft repair, age at SABG, age at taking cephalogram, surgeon, and total number of surgical interventions as independent variables were also created. 135 patients were included in the study - 70 patients (47 males and 23 females) had early SABG (E-SABG group) and 65 patients (40 males and 25 females) had late SABG (L-SABG group). Mean age at bone grafting procedure was 2.7 years (range 1.5-5.9, SD 1.1) and 10.3 years (range 6.1-18.8, SD 3.2) in E-SABG and LSABG group respectively. The variables describing the degree of maxillary growth restriction - SNA, Co-A, and PNS-A - were comparable in both groups (p = 0.707, 0.116, and 0.932, respectively). Regression models demonstrated that independent variables were not associated with the values of SNA angle, SNB angle, ANB angle, MP/SN angle, and Co-A distance (p = 0.761, 0.088, 0.249, 0.380, and 0.363, respectively). The percentages of oronasal fistula repair, VPI repair, repeated SABG, upper lip correction, rhinoplasty, orthognathic surgery were 22.9, 7.1, 15.7, 24.3, 42.9, 2.9 in E-SABG group and 27.7, 7.7, 9.2, 36.9, 47.7, 3.1 in L-SABG group respectively. Mean number of all surgical interventions was 3.2 in E-SABG and 3.4 in L-SABG group, respectively (p = 0.271). Considering the comparable maxillofacial morphology and burden of surgical care in matured patients after early and late SABG, the choice of timing of bone grafting surgery could be left to the discretion of the surgeon.
Keywords: Cleft Lip; Humans; Infant; kojenec; kefalometrie; Cephalometry; Female; lidé; Alveolar Bone Grafting; Unilateral cleft lip and palate; alveolární kostní štěp; předškolní dítě; Bone grafting; ženské pohlaví; Maxillofacial morphology; Male; Retrospective Studies; Cephalometric analysis; Cleft Palate; rozštěp patra; retrospektivní studie; rozštěp rtu; mužské pohlaví; Child, Preschool